La théologie politique des dévots Mathieu de Morgues et Michel de Marillac, opposants au cardinal de Richelieu - Maillet-Rao, Caroline (Renaissance and Reformation / Renaissance et Réforme, 2009)
The position of Chief Minister established by Cardinal Richelieu conjoined the minister’s role with the exercise of power. Since all final decisions remained with the king, this system of government was claimed as legitimate. Nevertheless, there were opponents of Richelieu’s ministry. The devout faction, represented by Mathieu de Morgues et Michel de Marillac, saw the new institution as a change to the current theory of monarchy, and thus open to legal challenge. On that basis, they laid out their opposition with a set of arguments. This essay analyzes the arguments, against Richelieu ’s ministry, that refer to the principles of monarchy.